A STUDY OF FACTORS AFFECTING CONSUMER ATTITUDE AND ADOPTION INTENTION OF SAMSUNG GEAR VR - Sri Wulan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to investigate the influence of perceived usefulness, perceived ease of use, perceived novelty and perceived enjoyment on consumer attitude and adoption intention of Samsung Gear VR. The primary data used in this study were collected from 140 respondents who have experienced in operating or using Samsung Gear VR, using a survey method by distributing online structured questionnaires. The collected data were analyzed using path analysis method using SPSS and AMOS software.The results show that perceived ease of use, perceived novelty and perceived enjoyment influence the consumer adoption intention through attitude, while perceived usefulness and perceived enjoyment have direct effects on adoption intention. Among those factors, perceived enjoyment is the most dominant factor that strongly affects both the consumers attitude and adoption intention of Samsung Gear VR. Based on the findings, marketers should improve the aspect of product related to its usefulness, easiness (system), novelty and more focus on enjoyment (features) to enhance the consumer attitude towards intention to adopt Samsung Gear VR.Keywords: Perceived Usefulness, Perceived Ease of Use, Perceived Novelty, Perceived Enjoyment, Consumer Attitude, Adoption Intention, Wearable Technology, Virtual Reality.